SUPERVISION OF THE ACTIVITIES OF ENTERPRISES WHICH OPERATE DUAL-USE GOODS (TECHNOLOGIES): CURRENT STATE AND CHALLENGES DYNAMICS - Mazur, Iryna; Zhelizko, Yuliia (Global Prosperity, 2021)
In this article, we revealed the dynamics of change of supervision over the development, production, export and use of dual-use goods (technologies) from the end of the XIX century to the beginning of the XXI century. We proved that during the whole period of the research, there was a strengthening of supervision in the field of solid waste, especially concerning enterprises that develop, manufacture, export and use dual-use goods (technologies). The reasons for this are changing trends in security and the economy. We identified modern problems of strengthening supervision over the development, production, export and use of weapons and dual-use goods (technologies). Furthermore, we identified four areas of problem formation: at the supranational level, at the national level, at the level of individual business entities, the introduction of new ways to strengthen supervision. Ukraine’s problems in this area are revealed separately, based on a study of the development of its supervision system over the development, production, export and use of weapons and dual-use goods (technologies).